Feminist epistemology after postmodernism: Critiquing science, technology and globalisation - Braidotti, Rosi (Interdisciplinary Science Reviews, 2007)
This article provides a reasoned overview of contemporary developments within feminist theories of the subject after the decline of postmodernist thought. It stresses the foundational importance of feminist situated epistemology, and hence of a brand of materialism that stresses embodiment and embedded perspectives. The article explores neo-materialist feminist theories in a number of areas, with special emphasis on science and technology studies and critiques of globalisation. It argues that the neo-materialist trend results in a new call for an ethics attuned to the complexity of our era.
Keywords: approches et analyses; bio-technologie; discipline; environnement; féminisme matérialiste; philosophie; postmodernisme; projet charge mentale; ressource en ligne; sciences humaines; thématiques; épistémologie